Enhanced UV–vis photoinduced hydrogen evolution of metalloporphyrin sensitized PSf/TiO2 MMMs by varying center metal ion complexed in porphyrin. (15th March 2022) - Chen, Yanting; Wang, Mingxia; Yan, Feng; Wang, Wei; Qu, Yuning; Fang, Hongbo; Cui, Zhenyu; He, Benqiao; Li, Jianxin
Graphical abstract: Highlights: MP12 -M3 MMMs photocatalyzed H2 evolution from water under UV–vis radiation. The H2 evolution ability shows increased order of NiP12 -M3 < ZnP12 -M3 < CuP12 -M3 . The total H2 evolution of CuP12 -M3 was 70.63 mmol/m 2 after 12 h irradiation. The kET and AQY at λ = 420 nm of CuP12 -M3 was 1.51 × 10 9 s −1 and 31.7 %, respectively. A green method was provided to enhanced H2 evolution by varying M 2+ complexed in THPP. Abstract: In order to produce hydrogen fuel in green and environmentally friendly method, a series of novel metal-5, 10, 15, 20- meso -tetra(p-hydroxypheny) porphyrin (MTHPP, M = Cu, Zn and Ni) mono-dispersedly functionalized MTHPP-sg-PSf/TiO2 mixed matrix membranes (MP12 -M3 MMMs) were prepared via the in-situ surface grafting. UV–Vis induced hydrogen evolution from water shows an increasing order of NiP12 -M3 < P12 -M3 < ZnP12 -M3 < CuP12 -M3, and the hydrogen production by CuP12 -M3 was up to 70.63 mmol/m 2, which is 7.25 times higher than that of control membrane without metal ion (P12 -M3 ). The apparent quantum yield (AQY) at λ = 420 nm of CuP12 -M3 was 31.7 %, which are better than most reported photocatalysts. Furthermore, the hydrogen evolution performance of the MP12 -M3 MMMs are higher than that of equivalent MTHPP-TiO2 powder, indicating that the porous membrane can immobilize porphyrin and TiO2 monodispersely to improve its catalytic performance significantly. Finally, the photocatalytic mechanism of the MP12 -M3 MMMs was explored by electrons transfer rate constant (kET ), excited state oxidation potential (EOX(dye*) ), electron spin resonance (ESR) and density functional theory (DFT). This work details the construction a photocatalytic membrane by novel surface modification method, which can be used for long-term photolysis of water to produce hydrogen and provide an effective strategy for improving hydrogen production performance.